ORGANIZATION OF SAFETY MEASURES IN THE HOSPITALITY INDUSTRY - Вівсюк, Ірина; Лук’янець, Алла (SWorldJournal, 2024)
The article examines issues and ways of organizing security measures in the hospitality industry. In the conditions of a global pandemic and a full-scale war on the territory of Ukraine, hotel and restaurant enterprises and tourist destinations were forc